Echocardiographic Evaluation of Right Ventricular Hypertrophy Regression After Total Correction of Tetralogy of Fallot in Pediatric Patients - Alauddin, Md.; Sunny, Mohammad Samir Azam; Rahman, Khan Mohammad Amanur; Hossain, Nawrin; Ahmed, Marina; Rahman, Mostafizur (Journal of Neonatal Surgery, 2025)
Background: Tetralogy of Fallot is a congenital heart defect characterized by right ventricular hypertrophy and other anatomical abnormalities that significantly impact postoperative cardiac function. The purpose of this study is to assess the regression of right ventricular hypertrophy following total surgical correction of TOF in pediatric patients using echocardiographic assessment. Aim of the study: The aim of the study was to evaluate the regression of right ventricular hypertrophy following total surgical correction of Tetralogy of Fallot in pediatric patients using serial echocardiographic assessment. Methods: This descriptive cross-sectional study was conducted at the Department of Cardiac Surgery, Bangladesh Medical University, Dhaka, from January 2024 to January 2025. Thirty pediatric TOF patients undergoing total correction were evaluated with serial echocardiography at baseline, 7th POD, 1 month, and 3 months to assess RV wall thickness, diameter, and systolic pressure. Paired t-tests analyzed changes using SPSS v26 (p < 0.05). Results: Among 30 pediatric TOF patients (mean age 5.53 ± 2.95 years; 60% male), preoperative RV hypertrophy (mean wall thickness 7.63 mm) and hypoxemia (SpO₂ < 85% in 56.7%) were common. By 3 months post-surgery, RV wall thickness decreased by 18.3% (to 6.23 mm), RV diameter by 12.4% (to 21.2 mm), and RV systolic pressure by 28.2% (to 34.8 mmHg; all p < 0.0001). The greatest RV regression (24.1%) occurred in the 1–3 year age group, highlighting better remodeling with earlier repair. Conclusion: Total correction of Tetralogy of Fallot in pediatric patients leads to significant right ventricular hypertrophic regression, especially when performed at a younger age.